Design and application of the multifunctional trolley for debridement and wound care (一种多功能清创车的设计与应用) - QIAN Bona (钱波娜); ZHU Shanli (朱珊莉); XU Yuanle (许远乐) (中西医结合护理, 2023)
This paper introduced the design and application of the multifunctional trolley for debridement and wound care. The trolley comprised of multiple functional components is effective to reduce manual operating workload and reduce occupational exposure. (清创车是临床常见的医疗器械装备。本文介绍一款多功能清创车的设计原理和使用方法, 通过多个部件的联合运作, 能够有效减少人工操作, 降低职业暴露风险。)